2018
DOI: 10.24884/1682-6655-2018-17-3-80-86
|View full text |Cite
|
Sign up to set email alerts
|

LDF method capabilities in the estimation of age-related features of the microcirculation system functioning

Abstract: The aim of this study was to assess the age-related features of the functioning of the microcirculation system using the LDF method. The estimation of parameters of microcirculation was performed in practically healthy persons of mature age in a one-stage study and in a prospective study in children aged 8 to 11 years. Stable indices of microcirculation were recorded at different stages of adulthood with maximal values in the middle of this age period. In the prospective study, significant changes in the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
0
0
2
Order By: Relevance
“…Thus, as studies have shown, in males and females there is a heterochrony of the values of MP and SD: at one age higher than the values of the studied females, and at anotherin young men. This fact reflects the general biological pattern of different maturation of the male and female body [14,15]. Thus, the values of MP from 17 to 19 years were higher in girls, in 20 years boys were ahead of this indicator, and at the age of 21 their values were almost the same.…”
Section: Research Resultsmentioning
confidence: 65%
“…Thus, as studies have shown, in males and females there is a heterochrony of the values of MP and SD: at one age higher than the values of the studied females, and at anotherin young men. This fact reflects the general biological pattern of different maturation of the male and female body [14,15]. Thus, the values of MP from 17 to 19 years were higher in girls, in 20 years boys were ahead of this indicator, and at the age of 21 their values were almost the same.…”
Section: Research Resultsmentioning
confidence: 65%
“…Эти показатели закономерно ниже на нижних конечностях по сравнению с таковыми на верхних конечностях, независимо от гендерных различий обследованных детей. Полученные данные совпадают с результатами других исследователей, определявших состояние микроциркуляции в различных сегментах верхних и нижних конечностей [18,19]. Более низкие значения ПМ на нижних конечностях обусловлены тем, что они находятся в иных гемодинамических условиях, по сравнению с верхними.…”
Section: результаты исследования и их обсуждениеunclassified
“…Обращает на себя внимание крайне низкая асимметрия ПМ на стопах как у мальчиков, так и у девочек. С одной стороны, это свидетельствует еще о незрелости механизмов модуляции тканевого кровотока у детей 6-7 лет [9,10,19], а с другой -о том, что асимметрия показателей микроциркуляции в дистальных сегментах конечностей во многом может зависеть от разной физиологической нагрузки на них [20]. Известны попытки объяснить причину лево-правосторонней асимметрии показателей микроциркуляции, исходя из асимметрии хиральных характеристик сосудов симметричных органов [21], однако это требует еще дополнительных исследований для обоснования возможности применения математического аппарата теории хаоса для определения степени хаотичности флаксмоций.…”
Section: результаты исследования и их обсуждениеunclassified
“…The cardiovascular system performs integrative functions in the body and influences the functioning of other body systems. Studies of regulation mechanisms at different levels of the circulatory system in children depending on their gender and age can serve to solve the issues of correction in cases of blood flow disorders [4,8]. The study of tissue blood flow, including capillaroscopy [3,6] and laser Doppler flowmetry [1,2] are of great importance.…”
Section: Introductionmentioning
confidence: 99%